Family needs of patients in intensive care unit a literature review - Wantiyah Wantiyah; Habibatus Khoirotin Ilmiah; Rismawan Adi Yunanto; Baskoro Setiputro; Ana Nistiandani (Media Keperawatan Indonesia, 2022)
The intensive care room is a room full of pressure for the patient being treated and the family caring for it and focuses more on the physical needs of the patient so that the family feels neglected by the service. Health services do not pay attention to family needs. To identify the needs of the patient's family in the intensive care unit. We used five databases, namely Google Scholar, Science Direct, PubMed, SpringerLink, and ProQuest using the PRISMA Flowchart for our study. The study design was cross-sectional, cohort and qualitative, year of publication 2017-2022, and discussed the needs of the patient's family in the intensive care room. A total of 13 articles were selected for analysis, examining 5 family needs, namely assurance, information, comfort, support and proximity. They were using instruments such as CCFNI, NMI, and NFNI. This instrument is proven to have been used globally to measure the needs of families in intensive care. Priority of family needs with CCFNI and NFNI instruments, namely assurance with proximity. Fulfilment of family needs using NMI instruments, information as a need that is met by health services. The priority of family needs is assurance so that it prioritizes physiological needs above other needs.